Role of multi-slice computed tomography in evaluation and management of intestinal obstruction - Waseem M., Raja; Rather, Zahid M.; Majid, Nighat Ara; Islam, M. Nazrull; Toktosunovich, Ydyrysova Ismatilla (International Surgery Journal, 2019)
Background: The purpose of this study is to evaluate the role of multi-slice computed tomography (CT) with reference to presence or absence of intestinal obstruction, level of obstruction, the cause of obstruction, and correlating with their clinical diagnosis. Methods: Patients were admitted directly from Out Patient Department or emergency department with complaints suggestive of intestinal obstruction. Computed tomography scan interpretations performed by experienced radiologists were compared with the final diagnosis that was made on the basis of information obtained clinically, by investigations, and by surgical findings. Results: Majority of patients were males 62%. Mean age 51.62±17.46 years. Majority presents with abdominal pain 94% and constipation 72%.The most common cause of obstruction was adhesion bands 18%.The pre CT diagnosis was changed because of CT findings in 28 patients. Only in 50 (89.28%) patients CT findings matched with intra-operative and cause of obstruction was also found, and in 6 (10.71%) patients intra-operative findings are different from CT findings. In bowel obstruction, the CT sensitivity was 89.28%, specificity 90.90%, positive predictive value 92.59%, negative predictive value 86.95% and accuracy 92.59%. Conclusions: We concluded that multi-slice CT is highly sensitive and specific in determining the presence, the cause and site of bowel obstruction, the site of obstruction and cause of obstruction. We recommended the use of CT scan when diagnosis between ileus and obstruction on the basis of clinical and plain radiographic are difficult or in patients in whome small bowel obstruction is diagnosed when conservative management is contemplated.